Mosquito Longevity, Vector Capacity, and Malaria Incidence in West Timor and Central Java, Indonesia. (15th November 2011) - Ndoen, Ermi; Wild, Clyde; Dale, Pat; Sipe, Neil; Dale, Mike
Abstract : The aim of this paper was to relate anopheline mosquito longevity to malaria incidence in two areas in Indonesia: West Timor and Central Java. We estimated the physiological age of females captured landing on humans or resting inside and outside buildings. The estimate was based on the state of the ovaries and was used to estimate longevity. The results showed that there were large differences between the two areas surveyed. In West Timor the longevity of the anophelines ranged from 13 to 23 days, sufficient for completing the intrinsic incubation cycle and for malaria transmission, whereas in Central Java the longevity was only 3 days, insufficient both for incubation and for transmission. We concluded that the West Timor study area had a greater risk of malaria transmission than that of Central Java and this was supported by village survey data that showed greater malaria incidence in West Timor than in Central Java.